Pelaksanaan dan Tantangan Program Tahfidz Qur’an di MTs N 1 Yogyakarta - Ma’ruf, Maulida Aprilia; Radino, Radino (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This study aims to examine the implementation of the Tahfidz Qur’an program, its supporting and inhibiting factors, intervention approaches, and the assessment results of students’ Qur’an memorization at MTs N 1 Yogyakarta.Method – A qualitative descriptive method was used in this study. The research informants included the vice-principal of curriculum, Tahfidz Qur’an coordinator, Tahfidz Qur’an teachers, admissions committee, and Tahfidz Qur’an students. Data were collected through interviews, observations, and documentation. Data validity was ensured using source and technique triangulation. Data analysis techniques consisted of data reduction, data presentation, and conclusion drawing.Findings – The Tahfidz Qur’an program is conducted from 05:45 to 07:15, with memorization sessions twice a week and muraja’ah (review) every two weeks. Supporting factors include support and cooperation from various parties, student motivation, a conducive environment, and the use of specific Qur’anic scripts. Inhibiting factors consist of inaccurate Qur’an recitations, laziness, challenging or similar verses, heavy schoolwork, tardiness, and talking with friends during lessons. Mitigation strategies to address these challenges include providing tahsin (correction of recitation), teacher motivation, patience, effective time management, punctuality, and focus on muraja’ah in class. The assessment results show that the average memorization achievement is categorized as good (67%), fluency as good (44%), articulation (makhraj) as good (53%), tajweed as good (54%), effort as very good (50%), and manners as very good (65%). Research Implications – This study offers a deeper insight into the implementation of Tahfidz programs in middle schools, which can be used to enhance the quality of religious education in similar institutions.